Gap Plasmon of Virus‐Templated Biohybrid Nanostructures Uplifting the Performance of Organic Optoelectronic Devices. Issue 11 (1st April 2020) - Lee, Hock Beng; Kim, Won‐Geun; Lee, Miso; Lee, Jong‐Min; He, Siwei; Kumar, Neetesh; Devaraj, Vasanthan; Choi, Eun Jung; Jeon, Il; Song, Myungkwan; Oh, Jin‐Woo; Kang, Jae‐Wook
Abstract: Plasmonic nanostructures, which exhibit prominent localized surface plasmon resonance (LSPR) properties, are highly desirable for organic solar cells (OSC) and organic light‐emitting diode (OLED) devices. In the present work, novel plasmonic bio‐nanostructures are successfully synthesized via the self‐densification of silver (Ag) and gold (Au) metallic nanoparticles (NPs) onto a genetically engineered M13 bacteriophage template. Owing to the unique charge selectivity of the peptide receptors on the M13 bacteriophage, the metallic NPs can be directly anchored onto the bacteriophage through charge‐driven interactions without binder/surfactant. The resulting Ag/AuNP‐M13 bio‐nanostructures display extraordinary gap‐plasmon effect as well as tremendously enhanced LSPR properties than the randomly dispersed Ag/Au NPs. The incorporation of Ag/AuNP‐M13 bio‐nanostructures tremendously improves the performance of both OSC and OLED devices. Specifically, a power conversion efficiency increment of 15.5% is recorded for the phage‐modified OSCs; whereas an external quantum efficiency increment of 22.6% is achieved for the phage‐modified OLEDs. Based on this environmentally benign virus‐template approach, various plasmonic/photonic bio‐nanostructures can be designed for diverse device applications. Abstract : Genetically modified, filamentous M13 bacteriophage demonstrates great performance as a biotemplate for the controlled densification of metallic nanoaparticles with designated nanogaps, thus enabling the formation of biohybrid nanostructure with prominent gap‐plasmon effect. The incorporation of these plasmonic bio‐nanostructures has contributed to significant improvement in the performance of organic solar cells and organic light‐emitting diode devices.